PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA BERBANTU KARTU QR CODE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 4 SD NEGERI CAKUNG TIMUR 05 PAGI - Rahma Indah Mawarni; Awalina Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low student motivation in learning photosynthesis material is influenced by the lack of innovation in instructional media. Therefore, it is necessary to develop a dioramabased learning media supported by QR code cards that present learning materials through engaging illustrations during the learning process. This study aims to develop QR code-assisted diorama media and to enhance students’ learning motivation. The research employed a Research and Development (R&D) method using the ADDIE model. The results showed that the QR code-assisted diorama media was deemed